Development of Batik Linggo as a featured product in Kendal - Endah Rita Sulistya Dewi; Maria Ulfah; Ary Susatyo Nugroho (Universitas Muhammadiyah Magelang, 2022)
The batik industry has grown fairly well in the Kendal region. The numerous studios and artisans in the batik business, including Batik Linggo Limbangan Kendal, demonstrate this. The batik motif that became the source of inspiration for Batik Linggo artists is a historical landmark in the shape of a Lingga stone with a floral design and daily community activities. The fundamental issue is that local traditions like Batik Linggo, has not developed into regional icons. Counseling and training must be provided in order for the Gonoharjo Limbangan village community to acquire the knowledge and abilities necessary to produce Batik Linggo on its own. In this community service program, three Batik Linggo motifs—the rice, clove seed, and coffee bean leaf motifs—were created and granted intellectual property rights. Additionally, natural dye paste preparation methods are taught to Batik Linggo artisans. the Batik Linggo website was also created which is expected to function as an online marketing tool.